2012
DOI: 10.1007/s13295-012-0030-0
|View full text |Cite
|
Sign up to set email alerts
|

Network influences on cortical plasticity

Abstract: Neuronal plasticity forms the basis of our life­long ability to learn and adapt to new chal­lenges. Plasticity in adulthood, however, is of­ten limited and learning becomes increasing­ly laborious. Using a combination of behav­ioral tests and imaging of brain activity, we investigate in the visual system of mice how learning and plasticity change in the course of aging and after lesions and modify the structure and function of nerve cell networks. We hope that answering these key questions not only helps to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…These changes include both functional as well as structural modifications and are considered to be fundamental for development (Berardi et al, 2015). Moreover, it was shown that while plastic changes may be well circumscribed, they still have repercussions in other areas of the CNS, distant or contiguous (Greifzu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These changes include both functional as well as structural modifications and are considered to be fundamental for development (Berardi et al, 2015). Moreover, it was shown that while plastic changes may be well circumscribed, they still have repercussions in other areas of the CNS, distant or contiguous (Greifzu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In V1 of C57Bl/6J mice, this OD-plasticity is maximal at 4 weeks of age, declines in 2-3 month old animals and is absent beyond PD110 (Espinosa and Stryker, 2012;Levelt and Hübener, 2012), even after longer deprivation times (Greifzu et al, 2012), if animals are raised in standard cages (SC). In critical period mice (PD19-32), 4 days of MD are sufficient to induce OD-shifts towards the open eye (Gordon and Stryker, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…While the binocular part of V1 receives input from both eyes, the monocular part of V1 receives input from the contralateral eye only. Figure modified from Greifzu et al (2012).…”
Section: Visual System and Od-plasticitymentioning
confidence: 99%